ON THE QUESTION OF THE CONCEPTUAL JUSTIFICATION OF CIVIL AND PATRIOTIC EDUCATION OF THE YOUTH OF THE NORTH CAUCASUS - Aitek Koychuev (Вестник Северо-Кавказского федерального университета, 2022)
This paper presents conceptual ideas, methodological foundations and principles of construction and implementation of civil and patriotic education of the youth of the North Caucasus. Characterized by historical, religious, political and socio-economic determinants of the existing problems of civil-patriotic education of youth in the region. It is proposed to improve the performance of a number of conditions of the process.